Art et guerison: Les rites de possession Mahamba lies a la Fecondite chez les Luv Ale de zambie - Wastiau, Boris (Afrika Focus, 1998)
This paper deals with a number of symbolic practices and art forms that have developed within rituals of possession known as mahamba in the upper Zambezi and Kasai area. I refer mostly to the Luvale of Zambia, among whom there are numerous mahamba, variously related to serious illness, sterility, madness, failure, social alienation or other ills. Presenting alternatively aspects of ad hoc therapeutic rituals, and"social drama,to borrow V. Turner's expression, or of religious cults, they are performed by both men and women. Mahamba can lead to initiation into a professional cast or simply serve to restore a possessed patient's physical health or social status. As rituals that are both 'religious' and 'therapeutic', they must be considered within the broad context of cosmology and medical knowledge. Here I will discuss the transforming role of certain artefacts and performances in mahamba rituals that aim at restoring female fertility. KEYWORDS: cult figure, tehrapeutic arts, possession cult, fertility ritual, Zambia